2020
DOI: 10.1136/bmjopen-2020-038607
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: BIOVASC-late, a prospective multicentred study of imaging and blood biomarkers of carotid plaque inflammation and risk of late vascular recurrence after non-severe stroke in Ireland

Abstract: PurposeInflammation is important in stroke. Anti-inflammatory therapy reduces vascular events in coronary patients. 18F-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) identifies plaque inflammation-related metabolism. However, long-term prospective cohort studies investigating the association between carotid plaque inflammation, identified on 18F-FDG PET and the risk of recurrent vascular events, have not yet been undertaken in patients with stroke.ParticipantsThe Biomarkers Imaging Vulnerable A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Certain limitations of our study merit mention. First, while FDG-PET appears to be a useful clinical adjunct, the high cost of FDG-PET and limited availability may affect the generalized applicability of our findings ( 18 ). Other modalities to quantify plaque inflammation such as magnetic resonance imaging with contrast may offer a cheaper alternative, but data regarding its use is limited ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Certain limitations of our study merit mention. First, while FDG-PET appears to be a useful clinical adjunct, the high cost of FDG-PET and limited availability may affect the generalized applicability of our findings ( 18 ). Other modalities to quantify plaque inflammation such as magnetic resonance imaging with contrast may offer a cheaper alternative, but data regarding its use is limited ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a validated technique for characterising luminal stenosis, plaque volume, and composition. Positron emission tomography (PET) using 18 F-fluorodeoxyglucose (FDG) has been validated for non-invasive imaging of inflammation-related plaque metabolism ( 5 , 6 ). Almost no data exist on the association between plaque inflammation imaged with PET and biomarkers of unstable plaque imaged with MRI in patients with recently symptomatic carotid atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fujimoto et al demonstrated that the uptake of 18F-NaF was related to the severity of ischemic vascular brain disease on MRI, which suggests that it may be useful in the risk assessment of cerebrovascular disease [ 180 ]. In this way, the Biomarkers Imaging Vulnerable Atherosclerosis in Symptomatic Carotid disease (BIOVASC) trial, involving patients with carotid stenosis and a recent stroke/transient ischemic attack, found that in patients with recent symptomatic carotid stenosis, plaque 18F-FDG uptake was associated with early recurrent stroke [ 181 ]. The study showed for the first time that plaque FDG uptake independently predicts early stroke after PET.…”
Section: Biomarkers Of Non-invasive Imagingmentioning
confidence: 99%